CORPORATE DIVERSIFICATION AND FINANCIAL PERFORMANCE OF CONGLOMERATE FIRMS IN NIGERIA - Mayowa Gabriel Ajao; George Abayomi KOKUMO-OYAKHIRE (Management Department, Faculty of Economics and Business, Universitas Jambi, 2021)
This study examined the effect of corporate diversification on the financial performance of conglomerate firms in Nigeria. The nine (9) conglomerates firms listed on the Nigerian Stock Exchange as of 2019 formed the population and sample size for this study from 2011 to 2019. Corporate diversification was measured by; product, operational and geographical diversification. Panel least-square analytical method was used. Two-panel co-integration models were developed for empirical analysis to measure financial performance using Return of Assets (Book Value) and Tobin's Q (Market Value). The study's findings revealed that product diversification has a positive impact on the financial performance of conglomerates in Nigeria. However, operational and geographical diversification showed a negative but significant relationship between corporate diversification and the financial performance of conglomerates in Nigeria. It was concluded that corporate diversification has a dominant-negative impact on financial performance. However, only one form of corporate diversification (product) was positively related to financial performance. Therefore, the study recommends that conglomerates focus more on implementing geographical diversification strategy than other types of diversification as it encompasses a great deal of product and services promotions, which is key to improving annual sales and product awareness.